Determinación de los niveles de presión sonora generados por el tráfico vehicular en plazas públicas del distrito de San Juan y Punchana, 2022 - Lopez Tello, Javier Enrique (2024)
The study was carried out in two public squares, with the purpose of determining the highest level of sound pressure generated by vehicular traffic in the districts of San Juan Bautista and Punchana 2022. It is a non-experimental, descriptive, analytical and transversal research, since it only Information was collected on the sound pressure level, the number and type of vehicles, the sampling was done at 03 critical road crossings in Plaza Miguel Grau and Plaza José Abelardo Quiñones, the data were collected by the person responsible for the study, with the appropriate equipment (sound meter) and the noise measurement methodology established in NTP-ISO 1996-12-2007, for 20 minutes in the morning, afternoon and night, during this period the counting of vehicles circulating through the points was also carried out. measurement, differentiating the types of vehicles, concluding that the type of vehicle that most frequently circulates in both places are similar, with motokars standing out as the most numerous, followed by motorcycles and cars and trucks successively. The number of vehicles that circulate in both squares under study, the Abelardo Quiñones square area is the one that concentrates the largest amount of traffic in the three time slots, but in the night slot the largest number of vehicles is recorded in relation to at the morning and midday average. The noise measurements (dB) in the three time slots of the three measurement points of the two places under evaluation exceed the maximum permissible limit (LMP) of 70 dB for commercial areas. The average noise measurements present a decreasing and increasing trend line as the monitoring time passes in which moments of increase or decrease in noise (dB) are recorded, but the general average of noise levels shows values above of the LMPs. This shows that Abelardo Quiñones Plaza concentrates the highest level of sound pressure generated by vehicular traffic, which is why the hypothesis of the present study is accepted.